Chance of a lifetime - Thomas, Jodi (Thomas, Jodi. Harmony novel., 2013)
Local librarian Emily Tomlinson must confront a long-hidden secret when someone from her past appears in the Texas town, while new lawyer Rick Matheson must protect himself from attempts on his life while he contemplates a new-found, and maybe true, love.